Usability Evaluation of a School Library OPAC Using Heuristic Evaluation and User Testing - Faradina Faradina; Taqwa Hariguna; Fandy Setyo Utomo (Asosiasi Doktor Sistem Informasi Indonesia, 2026)
This study evaluates the usability of the Online Public Access Catalog (OPAC) at SMK Negeri 1 Purwokerto to address the persistent gap between traditional library information architectures and the modern search behaviors of vocational students within the Kurikulum Merdeka ecosystem. The research aims to solve the problem of